Unwelcome and Unlawful : Sexual Harassment in the American Workplace - Gregory, Raymond F., 1927- (Book collections on Project MUSE., 2004)
Nearly every American woman will, at some point during her working life, be sexually harassed, according to Raymond F. Gregory, a lawyer specializing in employment and discrimination law. Unwelcome and Unlawful provides information for those victims as well as for those suffering same-sex harassment and for male victims of sexual harassment. Gregory analyzes sexual harassment from the perspective of existing federal law and describes the legal rights that may be asserted by victims of harassment to obtain either injunctive or monetary relief. Conduct of a sexual nature that occurs in normal workplace socialization is generally not unlawful, but it will be considered to have crossed the line of legality if it is unwelcome and is sufficiently severe or pervasive to undermine an employee's work life. Questions typically arising in a sexual harassment case include:*What types of workplace conduct are classified as sexually harassing?*When is sexual conduct considered unwelcome?*When is sexual conduct perceived as severe or pervasive?*What are the obligations of an employee to report acts of sexual harassment?*If sexual harassment is proven, what monetary damages and other relief may the victim expect to be awarded?*When is an employer liable for acts of sexual harassment committed by its workers and supervisors?*What privacy rights does an employee claiming sexual harassment have? By clarifying little-understood aspects of the law barring sexual harassment, the author presents an indispensable resource for victims seeking to learn what to expect from the legal system if they contest the actions of their harassers in the courts.